Effect of thyroid dysfunction on hematological parameters-retrospective study - T., Babhina Krishnan; Papaiah, Supriya (International Journal of Research in Medical Sciences, 2023)
Background: Thyroid gland is an important endocrine gland in the human body. Thyroid hormones are required for the appropriate development, metabolic balance, differentiation and physiological function of almost all tissues. The thyroid gland produces hormones such as triiodothyronine (T3) and tetraiodothyronine or thyroxine (T4). Under physiological settings, thyroid hormone influences hematological parameters. This study was done to evaluate the effect of various types of thyroid function abnormalities on different haematological parameters. Methods: This was a retrospective study which included 323 subjects who were grouped as hypothyroidism, hyperthyroidism, subclinical hypothyroidism and euthyroid groups. Two blood samples were collected from patients in EDTA tubes and plain tubes for estimation of hematological parameters and thyroid hormonal assay respectively. The results were analysed using SPSS software. Results: The mean age of patients is 34.50 years with females comprising about 89.16% of cases and males comprising 10.84% of cases. Analysis of data obtained showed that there was a significant statistical difference in TLC, MCHC, RDW, TSH, FT4 and euthyroid, hypothyroid, hyperthyroid and subclinical hypothyroid (p value <0.05) respectively. However, there was no significant correlation in Hb, PLT, RBC, PCV, MCV, MCH (p value >0.05) thyroid groups. Conclusions: The study found that thyroid diseases impacted female more frequently than males. Thyroid diseases were more common in age group of 18-28 years. Study also revealed a strong link between haematological parameters and thyroid dysfunction in patients.